Psychophysiological Responses to Cognitive and Physical Training in Obese Elderly - Naghavi, Nooshin; Taheri, Morteza; Irandoust, Khadijeh (International Journal of Sport Studies for Health, 2018)
Objectives: Increasing prevalence rate of anxiety disorders in elderly populations especially due to physical limitations has become a key concern for health authorities. Therefore, the objective of the study was to investigate the effects of cognitive and physical training on anxiety in the Elderly.Methods: 49 aged females (62.3 ± 2.6 years) with BMI of 35 - 49.99 kg/m2 were assigned to one of three groups: Cognitive (n = 17), yoga (n = 16) and control group (n = 16). The cognitive training protocol focusing on breathing techniques, autogenic training, imagery/visualization, included an 8-week period, three sessions a week. Yoga practices comprising Asana training, Pranaya training, and meditation were conducted 3 times a week, for 8 weeks. The State-Trait Anxiety Inventory was given before yoga practice and cognitive training. Biofeedback devices were used to monitor galvanic skin resistance and resting heart rate. The data were analyzed using independent t-test and one-way ANOVA test.Results: The results indicated that both cognitive and physical training had a significant difference on Anxiety in the training groups (P ≤ 0.05), while no significant change was found for control group (P ≥ 0.05). Furthermore, both training modes decreased the skin potential response (SPR) (P < 0.001). In addition, physical training group had lower resting heart rate after intervention compared to the cognitive and control groups (respectively, P = 0.04 and P = 0.001) lower heart rate and skin conductance level over the entire measurement period.Conclusions: It was concluded that the health benefits of yoga aren’t not specific to maintaining physical health, but also extends to lowering the anxiety in elderly with obesity. It was also suggested that cognitive training can mitigate the anxiety symptoms in the elderly while no physical changes were shown in cognitive training.